First finding of Trichinella pseudospiralis in the Neotropical region - Krivokapich, Silvio (2015)
Fil: Krivokapich, Silvio J. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Parasitología; Argentina.